A Systematic Literature Review: UTAUT In Fashion - Indarwati , Tias Andarini; Paramita, R.A. Sista; Rahayu, Imami Arum Tri; Islam, Muh Ariffudin (CV ODIS, 2023)
UTAUT better explains the various technological and contextual factors to behavioural intention in technology adoption in individual and organizational contexts. Based on an extensive summary and synthesis, an alternative theoretical model proposed is UTAUT, the most frequently used IS/IT adoption model. This study uses a systematic literature review by applying two stages. In the first stage, articles will be identified and included in the Prism Flow Diagram model. In the next stage, articles are analyzed based on research methods, UTAUT dimensions, and presentation of research results. Articles that discuss UTAUT cover the fields of banking, health, vehicles, and online shopping. Most sites have articles about mobile payments, health, and online shopping, while UTAUT's research in education, banking, and other fields is conducted in Asian and European countries. Analytical data collection methods are quantitative and qualitative. The UTAUT model has four fundamental constructs that influence behavioural intentions. A comprehensive overview of meta-UTAUT has not been studied in the context of chatbots in the service industry. There are five significant meta-UTAUT constructs (performance expectations, effort expectations, social influence, facilitating conditions, and attitudes) to identify trends in continuing intentions to use chatbot services. The Meta-UTAUT model is most appropriate for understanding cellular adoption because, on the one hand, it represents an integrated model with attitude as a new mediating variable. Behavioural intention to use the system is influenced by several factors, including perceived risk, perceived trust, perceived cost, and self-efficacy, so the Meta-UTAUT Model is the most appropriate model for understanding mobile adoption.